Inadequate completion of advance care directives by individuals with dementia: national audit of health and aged care facilities. Issue Volume 12:Issue e3(2022) (4th January 2021) - Bryant, Jamie; Sellars, Marcus; Sinclair, Craig; Detering, Karen; Buck, Kimberly; Waller, Amy; White, Ben; Nolte, Linda
Abstract : Objectives: (i) Describe the prevalence and type of advance care directives (ACDs) and other advance care planning (ACP) documentation completed by persons with dementia, healthcare providers and others on behalf of a person with dementia; (ii) identify the personal and ACP programme characteristics associated with having ACP documentation in the health record; (iii) identify the personal and ACP programme characteristics associated with having a self-completed ACD. Methods: A multicentre audit was undertaken in Australian hospitals, general practices and residential aged care facilities. Auditors extracted demographic and ACP data from the records of eligible patients. ACP programme characteristics were provided by a site representative. Logistic and multinomial regression were used respectively to examine the factors associated with completion of any ACP documentation, and self-completion of an ACD by persons with dementia. Results: A total of 1388 people with dementia (33.2%) from 96 sites were included. Overall, 60.8% (n=844) had ACP documentation; 31.6% (n=438) had a self-completed ACD and 29.3% (n=406) had an ACP document completed by a health professional or someone else on their behalf. Older participants were more likely to have ACP documented. Multivariate analyses indicated the odds of having self-completed ACP documents, compared with no advance care plan or ACP completed by someone else, were significantly influenced by age, country of birth, setting and whether the site had ACP training, policies or guidelines. Discussion: While 60% of people with dementia had some form of ACP documentation, only half of the cases in which ACP was documented included an ACD completed by the person themselves.